Acyl-CoA synthetase-4, a new regulator of mTOR and a potential therapeutic target for enhanced estrogen receptor function in receptor-positive and -negative breast cancer - Orlando, Ulises Daniel (2015)
Although the role of acyl-CoA synthetase 4 (ACSL4) in mediating an aggressive phenotype is well accepted, there is little evidence as to the early steps through which ACSL4 increases tumor growth and progression. In this study, and by means of the stable transfection of MCF-7 cells with ACSL4 using the tetracycline Tet-Off system (MCF-7 TetOff/ACSL4), we identify the mTOR pathway as one of the main specific signatures of ACSL4 expression and demonstrate the partial involvement of the lipoxygenase pathway in the activation of mTOR. The specificity of ACSL4 action on mTOR signaling is also determined by doxycycline inhibition of ACSL4 expression in MCF-7 Tet-Off/ACSL4 cells, by the expression of ACSL4 in the non-aggressive T47D breast cancer cell line and by knocking down this enzyme expression in the MDA-MB-231 breast cancer cells, which constitutively express ACSL4. ACSL4 regulates components of the two complexes of the mTOR pathway (mTORC1/2), along with upstream regulators and substrates. We show that mTOR inhibitor rapamycin and ACSL4 inhibitor rosiglitazone can act in combination to inhibit cell growth. In addition, we demonstrate a synergistic effect on cell growth inhibition by the combination of rosiglitazone and tamoxifen, an estrogen receptor α (ERα) inhibitor. Remarkably, this synergistic effect is also evident in the triple negative MDA-MB-231 cells in vitro and in vivo. These results suggest that ACSL4 could be a target to restore tumor hormone dependence in tumors with poor prognosis for disease-free and overall survival, in which no effective specifically targeted therapy is readily available.